Design of a range extension strategy for power decentralized fuel cell/battery electric vehicles. (21st September 2015) - Hwang, Jenn-Jiang; Hu, Jia-Sheng; Lin, Chih-Hong
Abstract: Range extended electric vehicle is proposed to improve the range anxiety that drivers have regarding the battery running out on electric vehicles. Current design has compensated for this shortcoming by cascading a gasoline/diesel generator with the battery to facilitate the range of an electric vehicle. Due to the zero-CO2 emission stipulations, utilizing fuel cells as generators raises concerns in society. This paper presents a fuzzy charging strategy for power decentralized fuel cell/battery electric vehicles. In comparison to the conventional switch control, the proposed approach plays the role of enhancing the battery's state of charge (SOC). This approach improves the quick loss problem of the system's SOC and thus can offer a longer driving range. Smooth steering experience and range extension are employed as the main indexes for development of the fuzzy rules, which are mainly based on the energy management in the urban driving model. Evaluation of the entire control system is performed by simulation, which demonstrates its feasibility and effectiveness. Highlights: Urban driving experience for FC-REEV is optimized and improved by fuzzy control. The range anxiety can be fully controlled under the proposed approach. We improves the battery's lifetime and energy efficiency on REEV/FC-REEV systems. Operators feel almost the same driving experience as the engine cars. The proposed scheme can also be applied to the power centralized electric vehicles.